Immobilization of lipase in calcium alginate beads for the study of butyl acetate synthesis / Mohd Zulkhairi Abdul Rahim - Abdul Rahim, Mohd Zulkhairi (2006)
Literature about lipase (EC 3.1.1.3) , immobilized enzyme, alginate and chitosan are presented in thi s thesis. Thi s study involved the use of free and immobilized Iipases to catalyse esterification reaction of short chain fatty acid and alcohol to produce short chain ester. Generally , it involved the optimization of conditions of esterification reaction of acetic acid and n-butanol and followed by comparison of properties of immobilized enzyme with those of free enzyme. Results showed that 14.3 mg lipase , 80 umol n-butanol , 160 umol acetic acid and 3.0 days reaction time at a temp erature of 40 DC were the optimum conditions for lipase - CAB in terms of enzyme loading , immobilized enzyme concentration, temperature, substrate concentration and reaction time respectively. Meanwhile, 0.8% w/v of chitosan solution was chosen for the stabilized calcium alginate beads. Results showed that product conversion increased by increasing the temperature up to 50 DC for Lipase CAB and Lipase - CCAB but not for free lipase. Thermal stability test showed that Lipase - CAB and Lipa se - CCAB remained stable against temperature up to 60 DC compared to free lipase which had the highest activity at 30°C. The studies of effects of n-buta nol concentrations showed that increased in concentration of n-butanol above 40 umol decreased the conversion of product for Lipase - CCAB and free lipase. Meanwhile, conversion of product was affected by increasing concentration of n-butan ol to 80flmol and above for Lipase - CAB . In the study of effect of acetic acid, it was found that increasing concentration of acetic acid abovel60 umol decreased the product conver sion for Lipase - CAB and free lipase. However , Lipase - CCAB was not affected by high concentration of acetic acid up to 200 umol, Kinetic param eters , Km & Vmax of immobilized lipases for n-butanol were lower in values when compared with Km & Vmax values for acetic acid . Results showed that there were no stati stically significant different specific activities among the three systems studied. Operational stability test was important for repeated applications in batch or in a continuous reactor. It was demon strated that the enzyme was still active for at least 5 cycle s. Thus it was proven that immobilized lipase and free lipase were able to catalyse synthesis of short chain esters under the condition s studied. Continuous proce sses studies showed immobilized lipase had potential for such synthes is but need further studies . Several recommendations for further studies have also been suggested.